Conditional Trigonometric Identities | kullabs.com
Notes, Exercises, Videos, Tests and Things to Remember on Conditional Trigonometric Identities

Please scroll down to get to the study materials.

## Note on Conditional Trigonometric Identities

• Note
• Things to remember
• Videos
• Exercise

Identities which are true under some given conditions are termed as conditional identities.

In this section, we will deal some trigonometric identities which are bound to the condition of the sum of the angles of a triangle i.e. A + B + C =π

Properties of supplementary and complementary angles

(i)  Since   A + B + C = π

Then,   A + B = π - C, B + C = π - A and A + C = π - B

Now,   sin(A + B) = sin(π - C) = sin C

sin(B + C) = sin( π - A) = sin A

sin(A + C) = sin(π -B) = sin B

Again, cos(A + B) = cos(π - ) = -cos C

cos(B + C) = cos(π - A) = -cos A

cos(A + C) = cos(π - B) = -cos B

Also,   tan(A + B) = tan(π- C) = -tan B

tan(B + C) = tan(π- A) = -tan A

tan(A + C) = tan(π - B) = -tan B

(ii) Since    A + B + C = π

Then,      $$\frac{A}{2}$$ + $$\frac{B}{2}$$ + $$\frac{C}{2}$$ = $$\frac{π}{2}$$. So, $$\frac{A + B}{2}$$ = $$\frac{π}{2}$$ - $$\frac{C}{2}$$, $$\frac{B + C}{2}$$ = $$\frac{π}{2}$$ - $$\frac{A}{2}$$ and $$\frac{A + C}{2}$$ = $$\frac{π}{2}$$ - $$\frac{B}{2}$$

Now,       sin($$\frac{A + B}{2}$$) = sin($$\frac{π}{2}$$ - $$\frac{C}{2}$$) = cos $$\frac{C}{2}$$

sin($$\frac{B + C}{2}$$) = sin($$\frac{π}{2}$$ - $$\frac{A}{2}$$) = cos $$\frac{A}{2}$$

sin($$\frac{A + C}{2}$$) = sin($$\frac{π}{2}$$ - $$\frac{B}{2}$$) = cos $$\frac{B}{2}$$

Again,      cos($$\frac{A + B}{2}$$) = cos($$\frac{π}{2}$$ - $$\frac{C}{2}$$) = sin $$\frac{C}{2}$$

cos($$\frac{A + C}{2}$$) = cos($$\frac{π}{2}$$ - $$\frac{B}{2}$$) = sin $$\frac{B}{2}$$

cos($$\frac{B + C}{2}$$) = cos($$\frac{π}{2}$$ - $$\frac{A}{2}$$) = sin $$\frac{A}{2}$$

Also,       tan($$\frac{A +B}{2}$$) = tan($$\frac{π}{2}$$ - $$\frac{C}{2}$$) = cot $$\frac{C}{2}$$

tan($$\frac{A + C}{2}$$) = tan($$\frac{π}{2}$$ - $$\frac{B}{2}$$) = cot $$\frac{B}{2}$$

tan($$\frac{B + C}{2}$$) = tan($$\frac{π}{2}$$ - $$\frac{B}{2}$$) = cot $$\frac{A}{2}$$

Conditional Trigonometric Identities

• Properties of supplementary and complementary angles
.

0%
• ## You scored /0

Forum Time Replies Report